Young people and an NHS participation worker reflect on their involvement in a creative, collaborative mental health research project. (15th July 2017) - Allan, Sophie; Davis-Steel, Kelly; Dunn, Fran; Dunn, Valerie
Abstract : Most UK child and adolescent mental health services (CAMHS) support young people up to the age of 17/18, at which point they are discharged, or transition to an adult service. This transition is often difficult for young people, as they also face the complex physical and psychosocial changes of adolescence. Transition from CAMHS is often poorly managed, with negative outcomes for young people. Improved preparation may improve both outcomes and experience. We worked with 17 young people and staff from three NHS mental health foundation trusts to co-produce the CAMHS Transition Preparation Programme (TPP), deliverable in routine NHS settings. We took a creative, participatory approach to maximize young people's involvement in the research. Young people steered the direction of the work, and were involved in decision-making and dissemination both nationally and within their trusts. In this commentary, two young participant–researchers and one NHS staff member describe the project from their perspectives.